EVALUASI PEMBELAJARAN JARAK JAUH DENGAN MITRA STKIP BIMA PRODI PENDIDIKAN EKONOMI: STRATEGI PEMBELAJARAN ONLINE BY MS TEAMS DAN PERMASALAHANNYA - Roni Wiranata; Triwilujeng Ayuningtyas (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The implementation of PJJ during the COVID-19 pandemic has a high effectiveness value for implementing learning activities at the higher education level in particular and all education providers in general. The method of learning at home for students in each institution is different, because the facilities owned are different, the economic conditions of students and their parents are also different. So the purpose of this research is to focus on understanding online learning problems for partner students in the implementation of PJJ funded by the Directorate of Learning and Student Affairs, to understand distance learning strategies with Ms Teams and to understand the problems. The methodology in this study uses a qualitative approach where the informants are partner students, namely STKIP Bima and STKIP PGRI Lumajang students. To find out the focus of this research, researchers conducted covert interviews that were inserted during lectures and closed interviews for STKIP PGRI Lumajang students, and always made observations to innovate PJJ for one semester. From the evaluation results during the Odd semester of Distance learning for the 2021/2022 academic year, it is known that distance learning is indeed very effective for campuses in urban areas or those with stable internet networks. However, this is in contrast to education providers whose areas have network difficulties. Not only that, the availability of electricity and equipment is also an obstacle during the implementation of this distance learning. In evaluating distance learning with online learning strategies based on MS Teams, it is hoped that it can help partner students to keep learning during the pandemic with this distance learning program. lectures. The most prominent problems during distance learning activities are network problems and the availability of internet quota if the implementation of online lectures uses video, another problem is that partner students have not been able to apply Ms Teams learning media with the users provided. So it is recommended for further PJJ training and in-depth socialization related to the use of Office 365 users on Ms Teams and students need to increase motivation to learn interest during online learning.Keywords: Distance Learning, MS Teams and Online Learning Strategies